Magnesium application improves the morphology, nutrients uptake, photosynthetic traits, and quality of tobacco (Nicotiana tabacum L.) under cold stress - Li, Jian; Muneer, Muhammad Atif; Sun, Aihua; Guo, Qinyu; Wang, Yuemin; Huang, Zhenrui; Li, Wenqing; Zheng, Chaoyuan (Frontiers in Plant Science, 2023)
Cold stress is one of the major constraints limiting the productivity of many important crops, including tobacco (Nicotiana tabacum L.) production and quality worldwide. However, the role of magnesium (Mg) nutrition in plants has been frequently overlooked, especially under cold stress, and Mg deficiency adversely affects plant growth and development. Here, we evaluated the influence of Mg under cold stress on tobacco morphology, nutrient uptake, photosynthetic and quality attributes. The tobacco plants were grown under different levels of cold stress, i.e., 8℃, 12℃, 16℃, including with a controlled temperature of 25℃, and evaluated their effects with Mg (+Mg) and without Mg (–Mg) application. Cold stress resulted in reduced plant growth. However, the +Mg alleviated the cold stress and significantly increased the plant biomass on an average of 17.8% for shoot fresh weight, 20.9% for root fresh weight, 15.7% for shoot dry weight, and 15.5% for root dry weight. Similarly, the nutrients uptake also increased on average for shoot-N (28.7%), root-N (22.4%), shoot-P (46.9%), root-P (7.2%), shoot-K (5.4%), root-K (28.9%), shoot-Mg (191.4%), root-Mg (187.2%) under cold stress with +Mg compared to –Mg. Mg application significantly boosted the photosynthetic activity (Pn 24.6%) and increased the chlorophyll contents (Chl-a (18.8%), Chl-b (25%), carotenoids (22.2%)) in the leaves under cold stress in comparison with –Mg treatment. Meanwhile, Mg application also improved the quality of tobacco, including starch and sucrose contents, on an average of 18.3% and 20.8%, respectively, compared to –Mg. The principal component analysis revealed that tobacco performance was optimum under +Mg treatment at 16℃. This study confirms that Mg application alleviates cold stress and substantially improves tobacco morphological indices, nutrient absorption, photosynthetic traits, and quality attributes. In short, the current findings suggest that Mg application may alleviate cold stress and improve tobacco growth and quality.